Conociendo las foicinhas líticas del poblado prehistórico de Leceia (Oeiras, Portugal) - Cardoso, João Luis (2020)
Bifacial tools made of flint are some of the most representative elements of the Late Neolithic-Chalcolithic in much of the western Iberia. In Portugal these pieces, traditionally called foicinhas, are currently known as "foliaceous blades". Many sites of this period are fortified settlements, Leceia being one of the best-known examples. Surprisingly, in spite of their abundance the lithic instruments in general, and foliaceous blades in particular, in sites of this period have not been studied in detail. Here we address the raw material, technology, morphology, and function of these tools. This allows us to evaluate the supply areas, the possible social relations established with other groups (based on the origin of certain types of flint), the technological capacity of the inhabitants of Leceia, and the function of some of these blades.